Determination of Acrylamide in Starchy Foods by RP-HPLC - Yongchun Wei (The International Journal of Multiphysics, 2024)
In order to establish a simple method for detecting acrylamide in food, this article optimizes the determination conditions, sample and processing conditions using high-performance liquid chromatography ultraviolet detector. The research results show that, the samples defatted by hexane, ultrasonic extraction in chloroform. The analytes were isolated by reversed phase high performance liquid chromatography on a C18(4.6×250mm，5μm) column and eluted with 5% methanol aqueous solution at a flow rate of 0.8mL/min. The detection wavelength was 210 nm, Quantitative analysis method was external standard method. The experimental results indicated that the linearity of the calibration curve was good in the range of 0.2μg/ml 2.5μg/ml (r=0.9991), and the recoveries of acrylamide from spiked samples by this method were within 87.6% 97.8% (n=5). The method was simple, accurate, reliable and suitable for the determination of acrylamide in potato chips, instant noodles, biscuits, bread and other starchy foods. Compared with traditional methods, this method does not rely on expensive Mass spectrometry detection equipment and is easily adopted by most laboratories, which is conducive to its promotion and application in the food testing industry.